RELEVANSI NILAI-NILAI TARI BEDAYA BONDHET DALAM PENDIDIKAN KARAKTER - Titik Putraningsih (Imaji, 2016)
This research aims to describe the relevance of the values in BedayaBondhetdance course in terms  of character education in Dance Education Department,Yogyakarta State University. This research uses descriptive qualitative approach based on written and oral data. The subject of this research is students of Dance Education Department in Faculty of Languages and Arts, year  2014.  The steps of this research involve observing, data collecting, interviewing, having written and unwritten documentation, data analyzing, and concluding.The result shows that (1) the relevance of the values in  BedayaBondhetdance course in terms of character educationinclude the values of politeness, patience, discipline, concentration, spirit, confidence, determination, cooperation, responsibility, respect, solidarity, consideration, honesty, justice, firmness, feeling of unity, and  getting closer to God; and  2) After getting the values ofBedayaBondhet  dance the students are expected to have better attitudes and behavior.